Evaporation of an R114/R21 falling liquid film: Experimental studies and modelling; International Communications in Heat and Mass Transfer; Vol. 151 - Antonov D. V. Dmitry Vladimirovich; Volodin O. A. Oleg Aleksandrovich; Pecherkin N. I. Nikolay Ivanovich; Pavlenko A. N. Aleksandr Nikolaevich; Sazhin S. S. Sergey Stepanovich (2024, 2024)
Changes in the molar fraction of the volatile component R114 during the evaporation of an R114/R21 refrigerant mixture film falling over a vertical heated cylinder are investigated both experimentally and numerically. Experiments were performed for inlet molar fractions of the volatile component in the range 4 to 16%. When heat was added to the flowing film from the wall, a decrease in the molar fraction of the volatile component in the mixture was observed. The results of experiments are analysed using the one-dimensional (1D) model of multicomponent liquid film heating/evaporation. In that model, the liquid film is assumed to be flat which allows us to use the 1D forms of the heat transfer and component diffusion equations. The analytical solutions to these equations are used at each timestep of the analysis. The analytical solutions to these equations at the end of the previous timestep are used as the initial conditions for the following timestep with adjusted values of the input parameters. This model is shown to be applicable to the analysis of flows at Reynolds numbers (based on the film thickness) less than about 78